Ocena stopnia zróżnicowania warunków pracy w Polsce na tle krajów Unii Europejskiej - Malina, Anna (Assessment of Work Conditions Differentation in Poland in Comparison with European Union Countries, 2007)
The paper presents results concerning work conditions in Poland and EU countries. The work conditions researches include such issues as: work time, work organization and safety, work salary, work disability and social benefits concerning accidents at work and occupational diseases. Based on the researches the Author discussed of work conditions differentiation and compared work safety status in Poland and EU countries regarding adjustment accommodation to European Union standards.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 210-218